Virtual playful strategies and problem solving on quantity in mathematics courses, in undergraduate students of a private university in metropolitan lima - Tocas Mena, Eusebio (2021)
The thesis: virtual playful strategies and problem solving on quantity in mathematics courses, in undergraduate students of a Private University in Metropolitan Lima, has as its main objective to determine the influence of the variables, the type of research is descriptive - correlational, with design is not experimental - cross-sectional and quantitative approach. The population is made up of 150 UPeU undergraduate students, who take mathematics courses or topics as a tool for their training in Architecture and Engineering careers. For data collection, an instrument of own elaboration was applied according to the current context. The instrument passed through the validation filter, yielding an evaluative result of good and the reliability of the instrument applicable for this, the statistical procedure was used: Cronbach's alpha coefficient. The research concludes that it is shown that there is a strong positive correlation during all the research, between the variables analyzed: Virtual playful strategies and Problem solving on quantity in mathematics courses, in undergraduate students from a private university in metropolitan Lima. In the same way, it is demonstrated that SI strong positive correlation between each dimension of the variables.